Fitokimia, Uji Antibakteri dan Uji Toksisitas dan Dari Ekstrak Daun Kayu Manis (Cinnamomum burmannii) Terhadap Tingkat Kematian Larva Artemia Salina Leach - L. Dangeubun, Jane; Serang, AM; Letsoin, Petrus; Maryani, Maryani (Universitas Batangahari Jambi, 2024)
.Â Cinnamon leaves have properties as lowering blood sugar levels, inhibiting bacterial growth. Cinnamon traditional medicine contains the largest component of chemical substances, namely cinnamic alcohol, coumarin, cinnamic acid, sinamaldehyde, anthocinin and essential oils with sugar, protein, simple fat, pectin and others. Furthermore, it is said that cinnamon has antimicrobial, antifungal, antiviral, antioxidant, antitumor, blood pressure lowering, cholesterol and has low fat compounds. The dominant polyphenolic compound in cinnamon leaves is from the aldehyde group, which has insulin-like activity and antioxidant activity.Â This study aims to determine the compounds contained in cinnamon leaves and antibacterial and toxicity testing of cinnamon leaves (Cinnamomum burmanni) was carried out to determine the effect on the mortality rate of Artemia salina Leach larvae. The results of toxicity testing of cinnamon leaf extract are known to be non-toxic and have an LC50 value of 128.6 ppm.Â From the results of antibacterial tests of cinnamon leaf extracts with methanol, ethyl acetate and N hexanes solvents, it is known that the highest inhibition is in leaf extracts using methanol solvents with a yield of 12% and inhibition of 5 mm, while phytochemical tests of cinnamon leaf water extracts contain Alkaloids, tannins, saponins and flavonoids, triterpenoids and flavonoids.